Defining the conditional basis of silicon phthalocyanine near-IR ligand exchange. Issue 28 (4th July 2018) - Anderson, Erin D.; Sova, Stacey; Ivanic, Joseph; Kelly, Lisa; Schnermann, Martin J.
Abstract : The near-IR light induced ligand exchange of silicon phthalocyanines involves a critical radical anion intermediate and is dependent on hypoxia and a reductant. Abstract : Bond cleavage reactions initiated by long-wavelength light are needed to extend the scope of the caged–uncaged paradigm into complex physiological settings. Axially unsymmetrical silicon phthalocyanines (SiPcs) undergo efficient release of phenol ligands in a reaction contingent on three factors – near-IR light (690 nm), hypoxia, and a thiol reductant. These studies detail efforts to define the mechanistic basis for this unique conditionally-dependent bond cleavage reaction. Spectroscopic studies provide evidence for the formation of a key phthalocyanine radical anion intermediate formed from the triplet state in a reductant-dependent manner. Computational chemistry studies indicate that phenol ligand solvolysis proceeds through a heptacoordinate silicon transition state and that this solvolytic process is favored following SiPc radical anion formation. These results provide insight regarding the central role that radical anion intermediates formed through photoinduced electron transfer with biological reductants can play in long-wavelength uncaging reactions.